Registration of 'Pakhtunkhwa‐2015' (PR‐103), a Spring Soft White Wheat Cultivar. Issue 3 (12th July 2018) - Ahmad, Gulzar; Ishaq, Muhammad; Jan, Masood; Afridi, Khilwat; Khalil, Ibni Amin; Shah, Irfan Ahmed; Saeed, Muhammad; Ahmad, Nazir
Abstract : 'Pakhtunkhwa‐2015' (PR‐103) (Reg. No. CV‐1145, PI 687336) is a bread wheat ( Triticum aestivum L.) cultivar developed by the Cereal Crops Research Institute (CCRI), Pirsabak Nowshera, Pakistan, and released in 2015 for cultivation in Khyber Pakhtunkhwa in particular and Pakistan in general for irrigated areas. It has high yield potential, resistance to yellow rust, and good quality for chapati making. Pakhtunkhwa‐2015 is an elite breeding line developed at the International Wheat and Maize Improvement Center (CIMMYT), with the parentage WBLL1*2/4/YACO/PBW65/3/KAUZ*2/TRAP//KAUZ. This line was tested in the Elite Spring Wheat Yield Trial during 2009–2010 as an entry at CCRI Pirsabak Nowshera. After testing in preliminary, advanced, and multilocation yield trials from 2009 to 2014 in different ecological zones in the country, Pakhtunkhwa‐2015 (tested as PR‐103) was identified as a superior line that performed better than the local checks and it was released as a new cultivar in 2015 by the Provincial Seed Council. Pakhtunkhwa‐2015 exhibits medium maturity, semi‐erect leaves, stiff stem, medium ear size, resistance to stripe and leaf rust, and excellent chapatti making quality. Its average yield potential (6257 kg ha −1 ) was greater than the local check cultivars ('Pirsabak‐2004', 'Pirsabak‐05', and 'Pirsabak‐08'). Varietal maintenance and seed multiplication was taken up in 2015 with the aim to provide 5000 kg pre‐basic seed to agriculture extension departments and seed companies for multiplication and distribution in the following year. Pakhtunkhwa‐2015 has been popular among the farming community of Khyber Pakhtunkhwa, and it adds to the diversity of germplasm and cultivars available for use in the irrigated areas of Pakistan, with significant yield improvement.